Selected econometric methods of modelling the world’s population - Rzymowski, Witold; Surowiec, Agnieszka (Wybrane metody modelowania liczby ludności świata, 2018)
Selected econometric methods of modelling the world’s population size based on historical data are presented in the paper. Periodical variables were used in the models proposed in the paper. Moreover, a logistic-type function was used in modelling. The purpose of the paper was to obtain a model describing the world’s population with the lowest possible maximal relative error and possibly the longest period of durability. In this work, 13,244 models from three families models were analyzed. Only a small part of such a large number of models satisfies the conditions of stability. The method of modelling the world’s population size allows to obtain models with maximal relative errors not exceeding 0.5%. Selected models were used to prediction of the world’s population up to 2050. The obtained results were compared with data published by the Organisation for Economic Co-operation and Development
Econometrics = Ekonometria, 2018, Vol. 22, No. 2, s. 34-44
Keywords: nonlinear models; estimation; maximal relative error; population; forecast; modele nieliniowe; estymacja parametrów strukturalnych; maksymalny błąd względny modelu; populacja; predykcja